Logistic Regression Analysis on the Determinants of Stunting among Children Aged 6-24 Months in Purworejo Regency, Central Java - Rakhmahayu, Atika; Dewi, Yulia Lanti Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: Stunting is a representation of the state of chronic malnutrition in the first 1000 days of life that occurred in the world at an incidence of 22.2% in 2017. Stunting in children has impact on morbidity and mortality, resulting in a long-term decline socio-economic productivity of the community. The purpose of this study was to analyze the determinants of stunting in children aged 6-24 months in Purworejo, Central Java. Subjects and Method: This was an analytic observational study with a case control design. It was conducted in 25 integrated community health posts (posyandu) in Purworejo, from October to December 2018. A sample 200 children under five was selected using by simple random sampling. The dependent variable was stunting. The independent variables were maternal mid-upper arm circumference (MUAC) at pregnancy, maternal education, paternal education, family income, family food allocation, infant birth weight, exclusive breastfeeding, complementary feeding (CF), posyandu strata, stunting monitoring at posyandu, and posyandu stunting intervention. The data was collected by questionnaire and analyzed by a multiple logistic regression. Results: Maternal MUAC at pregnancy ?23.5 cm (b= -1.56; 95% CI= 0.06 to 0.67; p = 0.009), high maternal education (b= -1.70; CI95% = 0.06 to 0.57; p = 0.003), high paternal education (b= -1.90; 95% CI= 0.05 to 0.51; p= 0.002), high family income (b= -1.85; 95% CI= 0.05 to 0.50; p = 0.002), family food allocation (b= -2.26; 95% CI= 0.03 to 0.37; p<0.001), birth weight ?2,500 g (b= -1.39; 95% CI= 0.08 to 0.83; p= 0.024), exclusive breastfeeding (b = -2.04; 95% CI= 0.04 to 0.48; p= 0.002), and adequate complementary feeding (b= -1.61; 95% CI= 0.06 to 0.65; p= 0.007) reduced the risk of stunting in children aged 6-24 months. Conclusions: Maternal MUAC at pregnancy ?23.5 cm, high maternal education, high paternal education, high family income, family food allocation, birth weight ?2,500 g, exclusive breastfeeding, and adequate complementary feeding reduce the risk of stunting in children aged 6-24 months. Keywords: stunting, determinants, children aged 6-24 months Correspondence: